High-dose levocetirizine for the treatment of refractory chronic spontaneous urticaria and the effect on the serum inositol triphosphate level. Issue 9 (September 2019) - Huang, Xianqiong; Li, Zhaoyang; Sun, Renshan
Objective: The second messenger inositol triphosphate (IP3) is involved in signal transduction in multiple cell types. We evaluated the effects of high-dose levocetirizine on chronic spontaneous urticaria (CSU) and examined the significance of serum IP3 level in the pathogenesis of CSU. Methods: Fifteen patients with refractory CSU were given oral levocetirizine at a dose of 15 mg once daily for 7 days, and treatment efficacy was determined using the Urticaria Activity Score and by evaluating wheal-and-erythema reactions and itching. The serum concentration of IP3 at specific time points was determined by enzyme-linked immunosorbent assay. Results: The mean serum concentration of IP3 was 43.54 ± 41.97 pg/mL prior to treatment, 18.40 ± 17.53 pg/mL after treatment, and 1.31 ± 0.92 pg/mL in a healthy control group. The mean concentration of IP3 was significantly higher before treatment than after treatment, and the level of IP3 in the patient group before and after treatment was significantly higher than that in the control group. Conclusion: High-dose levocetirizine was shown to be effective in the treatment of CSU. The level of serum IP3 was positively correlated with CSU activity, indicating that IP3 may play an important role in the pathogenesis of this condition.